Mantle-derived gaseous components in ore-forming fluids of the Xiangshan uranium deposit, Jiangxi province, China: Evidence from He, Ar and C isotopes - Hu, Rui-Zhong; Burnard, P.G.; Bi, Xian-Wu; Zhou, Mei-Fu; Peng, Jian-Tang; Su, Wen-Chao; Zhao, Jun-Hong (Chemical geology, 2009)
The Xiangshan U deposit, the largest hydrothermal U deposit in China, is hosted in late Jurassic felsic volcanic rocks although the U mineralization post dates the volcanics by at least 20 Ma. The mineralization coincides with intrusion of local mantle-derived mafic dykes formed during Cretaceous crustal extension in South China. Ore-forming fluids are rich in CO 2, and U in the fluid is thought to have been dissolved in the form of UO 2 (CO 3) 2 2− and UO 2 (CO 3) 3 4− complexes. This paper provides He and Ar isotope data of fluid inclusions in pyrites and C isotope data of calcites associated with U mineralization (pitchblende) in the Xiangshan U deposit. He isotopic compositions range between 0.1 and 2.0Ra (where Ra is the 3He/ 4He ratio of air = 1.39 × 10 − 6 ) and correlates with 40Ar/ 36Ar; although there is potential for significant 3He production via 6Li( n, α) 3H( β) 3He reactions in a U deposit (due to abundant neutrons), nucleogenic production cannot account for either the 3He concentration in these fluids, nor the correlations between He and Ar isotopic compositions. It is more likely that the high 3He/ 4He ratios represent trapped mantle-derived gases. A mantle origin for the volatiles of Xiangshan is consistent with the δ 13C values of calcites, which vary from − 3.5‰ to − 7.7‰, overlapping the range of mantle CO 2. The He, Ar and CO 2 characteristics of the ore-forming fluids responsible for the deposit are consistent with mixing between 3He- and CO 2-rich mantle-derived fluids and CO 2-poor meteoric fluids. These fluids were likely produced during Cretaceous extension and dyke intrusion which permitted mantle-derived CO 2 to migrate upward and remobilize U from the acid volcanic source rocks, resulting in the formation of the U deposit. Subsequent decay of U within the fluid inclusions has reduced the 3He/ 4He ratio, and variations in U/ 3He result in the range in 3He/ 4He observed with U/ 3He ratios in the range 5–17 × 10 3 likely corresponding to U concentrations in the fluids < 0.2 ppm.